2012
DOI: 10.1088/1741-2560/9/4/045005
|View full text |Cite
|
Sign up to set email alerts
|

Does bimodal stimulus presentation increase ERP components usable in BCIs?

Abstract: Event-related potential (ERP)-based brain-computer interfaces (BCIs) employ differences in brain responses to attended and ignored stimuli. Typically, visual stimuli are used. Tactile stimuli have recently been suggested as a gaze-independent alternative. Bimodal stimuli could evoke additional brain activity due to multisensory integration which may be of use in BCIs. We investigated the effect of visual-tactile stimulus presentation on the chain of ERP components, BCI performance (classification accuracies an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
35
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 54 publications
6
35
3
Order By: Relevance
“…To the best of our knowledge, only two other BCI-related studies investigated bimodal stimuli: visual-tactile stimuli (Brouwer et al, 2010), and audio-visual stimuli (Belitski et al, 2011). In both studies the authors reported increased classification accuracies (i.e., the percentage of correctly classified target responses) for bimodal compared to unimodal conditions, which is in line with the trend we reported in Thurlings et al (2012a). …”
Section: Introductionsupporting
confidence: 92%
See 3 more Smart Citations
“…To the best of our knowledge, only two other BCI-related studies investigated bimodal stimuli: visual-tactile stimuli (Brouwer et al, 2010), and audio-visual stimuli (Belitski et al, 2011). In both studies the authors reported increased classification accuracies (i.e., the percentage of correctly classified target responses) for bimodal compared to unimodal conditions, which is in line with the trend we reported in Thurlings et al (2012a). …”
Section: Introductionsupporting
confidence: 92%
“…BCI performance of tactile ERP-BCIs (Brouwer et al, 2010; Thurlings et al, 2012a,b) is generally lower than that of gaze-dependent BCIs (Thurlings et al, 2012a,b). In addition, when a BCI is used as a control device in the context of a dual-task, for example to navigate in a game, BCI performance is even lower than in BCI-only tasks (Thurlings et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This type of classifier is known to perform well on a wide range of ERP-BCI paradigms including those with visual, auditory and tactile stimuli [37], [47][49]. It was trained on the data of 30 labelled trials collected during one block of calibration.…”
Section: Methodsmentioning
confidence: 99%